Personnel competencies in the field of tourism personnel management - Yuldasheva, Dilnoza (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this paper has been analyzed personnel competencies in the field of tourism personnel management. By the author has been described the content of the competency-based approach from the point of view of the specific characteristics of employees in the tourism sector. In addition, this article analyzes the general classification of competencies, on the basis of which a model for the formation of universal competencies of tourism employees has been developed. The purpose of the study is to create a model for the formation of universal competencies of employees at tourism enterprises. The study was carried out on the basis of content analysis of scientific works and methods devoted to the problems of forming and assessing universal competencies in tourism enterprises.